Metabolic, reproductive, and performance evaluation in primiparous Nellore beef cows under grazing with different ages at breeding - Vital, Mariana da Natividade Ferreira (2021)
The objective of this study was to evaluate the metabolic, reproductive and performance differences of primiparous Nellore cows, which became pregnant at 14 or 24 months. Thirty- eight primiparous Nellore cows with 200 ± 30 days of gestation were used, divided into two treatments: 14 - animals that became pregnant at 14 months of age, and 24 - animals that became pregnant at 24 months of age. The animals received 1.5 kg / day of supplement (36% CP) from prepartum until the end of the breeding season, after this period, cows and calves received mineral mixture ad libitum. To evaluate productive performance, cows were weighed and evaluated for body condition score (BSC), and calves were weighed at birth, at 45, 95,160, 220 days and at weaning. Blood samples were taken on the average 15 days before parturition, and on days 30, 60, 120, 240 days postpartum to measure glucose, total proteins, albumin, urea, beta-hydroxybutyrate (β-OHB) and non-esterified fatty acids (NEFA), progesterone at 30 and 45 postpartum and for insulin-like growth factor-1 at prepartum, 60 and 240 days postpartum., Milk collections were done at 60, 120 and 240 days postpartum. The data were analyzed using the GLIMMIX procedures in the SAS, adopting 0.05 as a critical level of probability for type I error. There was interaction (P<0.01) between the factors gestation age and parturition data- point for body weight, average daily gain and milk yield and Longissimus muscle. There was effect of the parturition data-point (P<0.01) for the BSC and thickness of the Longissimus muscle. Glucose, urea, total proteins, albumin and non-esterified fatty acids were affected (P<0.01) by the parturition data-point. There was effect of the parturition time-point (P<0.01) for β-OHB. No difference was found (P>0.05) in the IGF-1 options, however a difference was observed for the progesterone motors (P<0.01). Parturition time-point affected (P<0.01) calf weights. There was no difference (P>0.05) for gestation age and parturition time-point. It was concluded that primiparous cows that became pregnant at 14 or 24 months of age have different nutritional and metabolic responses. However, cows that have become pregnant at 14 months will wean another calf during its productive life. Keywords: Animal production. Beef cattle. Primiparous beef cows.